Deep Venous Thrombosis of the Upper and Lower Extremity. Issue 3 (July 2017) - Hattab, Yousef; Küng, Sarah; Fasanya, Adebayo; Ma, Kiet; Singh, Anil C.; DuMont, Tiffany
Abstract : Upper and lower extremity deep venous thrombosis (DVT) is defined as a blood clot within the deep veins of the affected extremities. These blood clots can either occur spontaneously or be associated with specific risk factors. Regardless of the cause, DVT is associated with significant morbidity and mortality and has the potential for lethal complications. The most notable complication is the potential for development of pulmonary embolism from a lower extremity DVT. As studies have reported, more than 90% of acute pulmonary emboli arise from the proximal veins. Venous thromboembolism is also associated with a significant economic burden on the health care system and the individual patient. In this article, we review DVT of the upper and lower extremity including risk factors, signs and symptoms, diagnosis, and management.